PENGARUH KONTEN MEDIA BROSUR TERHADAP PENGAMBILAN KEPUTUSAN KONSUMEN DI KREDITPLUS CABANG BANJARMASIN - Aminah, Siti; Ramadhani, Muhammad Muthahhari (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
Brochure is a tool for the promotion of goods, services, etc., which is also interpreted by official publication tools to companies in the form of prints, which contain various information about a product, service, program, and so on that is addressed to a specific target market or target. The purpose of this study is to examine the effect of the use of printed or online brochures on consumer purchasing decisions. The research approach conducted with Quantitative explorative with research location in Banjarmasin City and research sample is 348 CreditPlus customers covering 5 sub-districts in Banjarmasin City. Based on the results of the study showed that the R value of 0.640 is located at intervals 0.60-0.799 which are strongly interpreted. So the relationship between the Brochure Promotion Content variable and the consumer’s purchasing decision has a strong level of relationship. The brochure promotional content variable has a Fhitung value of > Ftabel (241,288 > 3,868). Thus the Brochure Media consists of three dimensions namely Layout, Size, Frequency simultaneously (simultaneously) there is an influence on the variables of Customer Decisions. In addition, the value of P of 0.000 < 0.05. Where, this shows that Media Brochure (X) KreditPlus to Customer Decision (Y) PT Finansia Multi Finance Kota Banjarmasin significantly affects. In addition, the results of a simple regression test obtained a correlation coefficient value or R value indicates the magnitude of the relationship between the brochure promotion content variable and the Customer Purchase Decision in using the service of 0.640 or 64.0% which is in the Strong category. The hypothesis states that Ha was accepted and H0 rejected. Thus, Varibel Media Brochure KreditPlus PT. Finansia Multi Finance significantly affects the Variables of Customer Decisions in using KreditPlus services in Banjarmasin City